(untitled) (Acta Scientiarum. Human and Social Sciences, 2022)
If myths have been narrated since time immemorial, this study argues that a novel kind of political myth has emerged over the past decades that has been adapted to a specifically modern significance and function. To account for the appearance of this novel form of political myth, I investigate the role of the mass media. In this perspective, the development and technological advance of the mass media has brought about a transformation in the modes of public experience and remembrance and a corresponding metamorphosis in the specific character of public space that lends to contemporary political myth its unique significance and function